Long-Term Performance of Primary and Secondary Electroactive Biofilms Using Layered Corrugated Carbon Electrodes - Baudler, André; Riedl, Sebastian; Schröder, Uwe (Frontiers in Energy Research, 2014)
The performance of primary and secondary electroactive biofilms grown on layered corrugated carbon electrodes was studied over a period of several months. With an average projected current density of 6.7 mA cm-2 the studied secondary electroactive biofilms outperformed the primary biofilms (3.0 mA cm-2) over the entire experimental period. At the same time both, primary and secondary biofilms, exhibited a constant Coulomb efficiency of about 89 %. The study further illustrates that three-dimensional electrodes such as layered corrugated carbon (LCC) allow a sustained long-term performance without significant decrease in electrode performance.